2009
DOI: 10.1097/ta.0b013e31819d8695
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Injury Reduction From Ocular Protection Use in Current Combat Operations

Abstract: This study suggests that the military combat eye protection used by military personnel during current combat operations has resulted in significantly fewer and less severe ocular injuries. Further, results from this study may also suggest that Department of Defense educational programs may have been successful in increasing eye protection compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 12 publications
2
33
0
1
Order By: Relevance
“…The anatomic distribution of the wounds matched the bulletproof vests and helmets worn by the soldiers: almost all of them suffered lower and upper extremity wounds, with the head, chest, and abdomen involved to a much lesser extent [17]. The high rate of ocular injuries reflects the soldiers' consistent failure to use protective eyewear: soldiers reportedly prefer not to use protective eyewear because it limits their field of vision [18], thus ocular injuries which can be prevented have devastating consequences [19].…”
Section: Discussionmentioning
confidence: 96%
“…The anatomic distribution of the wounds matched the bulletproof vests and helmets worn by the soldiers: almost all of them suffered lower and upper extremity wounds, with the head, chest, and abdomen involved to a much lesser extent [17]. The high rate of ocular injuries reflects the soldiers' consistent failure to use protective eyewear: soldiers reportedly prefer not to use protective eyewear because it limits their field of vision [18], thus ocular injuries which can be prevented have devastating consequences [19].…”
Section: Discussionmentioning
confidence: 96%
“…A recent study found reduced eye injury rates from 26% of those without eye protection to 17% among those using it. 18 We managed the challenge of providing highly technical eye care to service personnel in two theatresof-war. This has been through good teamwork with the deployed hospitals and the aeromedical evacuation services.…”
Section: Discussionmentioning
confidence: 99%
“…Eye injuries come at high cost to society [4,5] and can be reduced by the use of protective gear [6,7].…”
Section: Introductionmentioning
confidence: 99%